Peran Kaidah Fikih dalam Aktualisasi Hukum Islam: Studi Fatwa Yusuf Al-Qaradawi tentang Fiqh Al-Aqalliyat - Mun'im, Zainul (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
Fiqh as a product of Islamic law must always be up to date to become a religious solution for society. This fact requires scholars to have high creativity in doing ijtihad so that actualizing of Islamic law can be realized perfectly in today's contemporary era. One of the scholars who focus on the actualization of Islamic law is YuÃŒâ€žsuf al-QaradÃŒÂ£aÃŒâ€žwiÃŒâ€ž. His fatwas, which contain actualizations of Islamic law, are fatwas on Muslim minority issues (fiqh al-aqalliyaÃŒâ€žt). This study highlights the role of Islamic legal maxims (al-qawaÃŒâ€žid al-fiqhiyyah) in al-QaraÃ¡Â¸ÂÃ„ÂwÃ„Â«'s fatwa on fiqh al-aqalliyaÃŒâ€žt. The data comes from books and articles related to the theme. This research proves that Islamic legal maxims have a dominant role in the methodology of al-QaradÃŒÂ£aÃŒâ€žwiÃŒâ€žÃ¢â‚¬â„¢s ijtihad. In establishing his fatwa, al-QaradÃŒÂ£aÃŒâ€žwiÃŒâ€ž based the argument on the opinion of the islamic scholars in accordance to the basic values of fiqh principles. Therefore, his fatwa can be an actual solution for minority Muslim communities in Western countries. Thus, Islamic legal maxims (al-qawaÃŒâ€žid al-fiqhiyyah) play a role in controlling and systematizing the laws around fiqh al-Ã¢â‚¬ËœaqalliyÃ„Ât so that it always leads to convenience and avoids difficulties.